Effects of Financial Statement on Financial Decision of Listed Deposit Money Banks in Nigeria - Oluwayemisi, Ali- Momoh Betty; Samson, Fajuyagbe Bamikole; Favour, Ahmed Aminat (Acta Universitatis Danubius. Œconomica, 2022)
The research analyzed the influence of financial statements on financial decisions of listed deposit money bank in Nigeria. The research employed 14 deposit money banks that were carefully chosen from among the Nigerian stock exchange's 21 deposit money banks. The data for the research was gathered from the annual reports of the tested banks during a 13-year period, from 2007 to 2020. The data was examined utilizing descriptive and inferential research methodologies. Mean analysis, measure of dispersion, minimum and maximum analysis were among the descriptive analyses performed in the study, followed by correlation analysis, pooled OLS estimation, fixed effect estimation, random effect estimation, and post estimation tests such as restricted F-test, Hausman test, and Pesaran cross sectional independence. Asset tangibility has a favorable but negligible influence on deposit money bank capital structure decisions in Nigeria, according to the study's results. It was also shown that asset tangibility has a negative and minor impact on deposit money institutions' liquidity decisions in Nigeria. As a result, it is clear that asset tangibility influences deposit money bank financial decisions in Nigeria. Credit risk has a positive but negligible influence on deposit money bank capital structure decisions in Nigeria, but a negative but large effect on deposit money bank liquidity decisions, according to the research. Assets and liabilities have a mixed influence on deposit money banks' financial decisions in Nigeria, according to the research. The study concluded that deposit money banks in Nigeria should increase the tangibility of their assets, as this will provide investors and depositors with the assurance that their deposits and investments are safe as long as the value of the company's tangible assets exceeds the amount of their risk. This will be used as collateral to get additional cash from creditors, allowing banks to make better capital structure decisions. In addition, deposit money bank management in Nigeria could explore using mild debt in their capital structure components rather than equity. This is due to the fact that interest payments on debt obligations are tax deductible, whilst dividends paid to shareholders are not.